Implementasi Profil Pelajar Pancasila dalam Pembelajaran IPS - Ilhamdi Yusra (Tarikhuna: Journal of History and History Education, 2023)
This study aims to describe the implementation of the Pancasila Student Profile in Social Studies learning, which consists of the methods adopted to strengthen character in accordance with the Pancasila Student Profile, and the supporting and inhibiting factors for the implementation of the Pancasila Student Profile in Social Studies learning at Adabiah Padang Middle School. This research uses a qualitative type. This research uses data collection techniques through interviews, observation, and documentation. Data analysis was carried out through three stages, namely: data reduction, data presentation, and drawing conclusions and verification. From the research results it is known that 4 of the 6 indicators for Pancasila student profiles are the focus of strengthening social studies teachers at Adabiah Middle School, including faith and piety to God Almighty, Global Diversity, Cooperation and Critical Reasoning. The implementation of the 4 Pancasila Student profiles which are the focus is reflected in every activity in the school. The Social Sciences teacher implements Pancasila student profile indicators of faith and piety to God Almighty by integrating the Koran with Social Sciences material in every lesson accompanied by life advice. Implementation of global diversity by emphasizing the importance of unity in diversity, implementing collaboration by habituating learning activities using collaborative strategies, and implementing critical reasoning by confronting students with various phenomena and providing solutions to phenomena that occur.